Die Verordnung (EU) 2017/746 (IVDR) in der Praxis: Umsetzung von Anhang I in der Pathologie - Kahles, Andy; Goldschmid, Hannah; Volckmar, Anna-Lena; Plöger, Carolin; Kazdal, Daniel; Penzel, Roland; Budczies, Jan; Flechtenmacher, Christa; Gassner, Ulrich M.; Brueggemann, Monika; Vogeser, Michael; Schirmacher, Peter; et al. (Die Pathologie, 2023)
Background: Regulation (EU) 2017/746 on in vitro diagnostic medical devices (IVDR) imposes several conditions on pathology institutes that develop and use in-house in vitro diagnostic medical devices (IH-IVDs). However, not all of these conditions need to be implemented immediately after the IVDR entered into force on 26 May 2022. Based on an amending regulation of the European Parliament and the Council of the European Union, the requirements for IH-IVDs will be phased in. Conformity with the essential safety and performance requirements of annex I must be ensured from May 2022. Objectives: With this article, we would like to present the practical implementation of the currently valid conditions for IH-IVDs at the Institute of Pathology at the University Hospital of Heidelberg, in order to provide possible assistance to other institutions. Conclusions: In addition to the intensive work on the requirements for IH-IVDs, several guidance documents and handouts provide orientation for the implementation and harmonisation of the requirements for healthcare institutions mentioned in Article 5 (5). Exchange in academic network structures is also of great importance for the interpretation and practical implementation of the IVDR. For university and nonuniversity institutions, ensuring conformity with the IVDR represents a further challenge in terms of personnel and time, in addition to the essential tasks of patient care, teaching and research and the further development of methods for optimal and targeted diagnostics, as well as the maintenance of the constantly evolving quality management system.
Gesehen am 27.02.2025